Employee perceived overqualification and innovation performance: the roles of self-oriented perfectionism and job crafting - Jiang, Bing; Qiu, Hongxin; Liu, Siyi; Zhang, Ji (Frontiers in Psychology, 2024)
Leveraging the trait activation theory, the study constructs a model featuring moderated chain mediation to explore how perceived overqualification influences employee innovation performance. After conducting two surveys with Chinese employees, this study collects 363 valid questionnaires. The findings reveal that perceived overqualification is positively related to employee innovation performance. Both self-oriented perfectionism and job crafting are partial mediators between perceived overqualification and innovation performance, and they collectively play a chain mediating role. Furthermore, independent self-construction positively moderates the link between perceived overqualification and self-oriented perfectionism, and informal status positively moderates the relationship between job crafting and employee innovation performance. Additionally, the indirect influence of perceived overqualification on employee innovation performance is moderated by independent self-construction and informal status. This study adds to the current body of literature on perceived overqualification and offers practical implications for organizations aiming to enhance innovation performance.